The effect of climatic elements on the efficiency of land roads in Dhi Qar Governorate - Ibrahim, علي علي حسن (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
The climate is one of the important natural factors affecting human comfort and health, and it has been shown through the research hypotheses that the climatic elements have clear negative effects on the efficiency of operating the road network in Dhi Qar Governorate, but the level of these effects has varied between one climatic element and another, as the annual average temperature rises And its decrease during the summer and winter seasons has left its side effects on the daily movement of transport and traffic, as well as the precipitation had a similar negative role also on the movement of transport by causing a lot of mechanical breakdowns of vehicles as well as its direct role in the occurrence of many serious traffic accidents. As for the elements of wind and dust storms, their effects were clearly evident over the frontal vision of the drivers, and thus obstructed traffic and lengthened the travel time taken to reach the destinations. The same applies to the fog element, which is clearly active during the early hours of the morning on some days of the year